The area of the Hudna countryside between the influence of sheikhdoms and tribal alliances in the late Ottoman era - Birem, kamal (The Algerian Historical Journal, 2026)
Durant of the period of time and the beginning of French occupation, the vast city of our country has a place with tribal formations and alliances that influence the nature of the tribal society and its composition in the region and its relations with the autorits that pass through them. the region. These tribal formations have been confronted and have contributed to the emergence of certain tribal divisions that have transformed their allies and enemies.What is the nature of Hodna's tribal society, comment if the three rows form in your domain and what is the nature of relations How do you engage with the auto policy and the auto policy spirit of the region? Our essays respond the case. This contribution is added to the glossary of certain documents in local archives and elsewhere.